Implementation of prisoner independence guidance in class 1 Cirebon prison - Hidayat, Risyal Hardiyanto; Pujiono, Dedy Wasis; Waluyadi, Waluyadi; Sanusi, Sanusi (Edelweiss Applied Science and Technology, 2025)
Prisons (Lapas) play an important role in society by rehabilitating and developing problematic citizens. Various programs are implemented by prisons to help prisoners become independent and better individuals after their prison terms. Therefore, this research aims to determine the extent of the implementation of the prisoner self-reliance program in Cirebon Class 1 Prison and the obstacles faced. This research employs descriptive qualitative methods. The data collection techniques used were interviews and observations. The instruments for data collection included interview and observation sheets. Additionally, the sources for this research comprised prisoners, prison officers, and other related parties involved in the independence development program at Cirebon Class 1 Prison. The results indicate that out of the 13 programs carried out, 11 programs—including convection, embroidery, rattan weaving, doormat making, agriculture and animal husbandry, welding, catering, laundry, barbering, handicrafts, and screen printing—are functioning properly. However, two other programs, woodworking and the production of boal and fishing nets, need revitalization. Several obstacles affect production and marketing during implementation, including a lack of human resources, insufficient facilities and infrastructure, inadequate marketing of production results, reliance on external orders that hinder work activities, and a lack of capital for manufacturing and optimizing work activities.